Cara Menyikat Gigi dengan Melakukan Penyuluhan Kesehatan Gigi pada Anak Inklusi (Studi di Sekolah Inklusi Galuh Handayani Surabaya) - Ni Luh Arminita Pratiwi; Silvia Prasetyowati; Sri Hidayati; Agus Marjianto (Akademi Keperawatan Yarsi Samarinda, 2026)
Inclusive children are at a higher risk of experiencing oral health problems due to physical, cognitive, and motor limitations that affect their ability to perform proper toothbrushing independently. Dental health education is a promotive intervention that may improve toothbrushing skills among inclusive children. Objective: To analyze the effect of dental health education on toothbrushing skills among inclusive children at Galuh Handayani Inclusive School, Surabaya. Methods: This study employed a pre-experimental design using a one-group pretest-posttest approach. A total of 38 inclusive children were selected through purposive sampling. The intervention consisted of dental health education using a demonstration method. Toothbrushing skills were assessed using an observation checklist before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. Results: Before the intervention, most participants were categorized as requiring guidance (68.8%). Following the intervention, the majority demonstrated improved toothbrushing skills, with 60.6% categorized as very good and 39.4% as fair. The Wilcoxon Signed Rank Test revealed a statistically significant difference between pretest and posttest scores (p = 0.000; p < 0.05). Conclusion: Dental health education delivered through the demonstration method was effective in improving toothbrushing skills among inclusive children at Galuh Handayani Inclusive School, Surabaya.